Efficacy and effectiveness of live attenuated influenza vaccine in school-age children. (3rd October 2015) - Coelingh, Kathleen; Olajide, Ifedapo Rosemary; MacDonald, Peter; Yogev, Ram
Abstract : Evidence of high efficacy of live attenuated influenza vaccine (LAIV) from randomized controlled trials is strong for children 2–6 years of age, but fewer data exist for older school-age children. We reviewed the published data on efficacy and effectiveness of LAIV in children ≥5 years. QUOSA (Elsevier database) was searched for articles published from January 1990 to June 2014 that included 'FluMist', 'LAIV', 'CAIV', 'cold adapted influenza vaccine', 'live attenuated influenza vaccine', 'live attenuated cold adapted' or 'flu mist'. Studies evaluated included randomized controlled trials, effectiveness and indirect protection studies. This review demonstrates that LAIV has considerable efficacy and effectiveness in school-age children.